Dinamika Bahasa Indonesia di Era Digital : Antara Perkembangan Linguistik dan Tantangan Preservasi - Esa Peggy Nerida Manurung; Jesika Lolo Karina Manik; Gracesela Septiana Sibuea; M. Surip (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
The digital era has brought significant changes to the use of Indonesian in various aspects of life, including daily communication, the academic world, as well as the creative industry and tourism. Phenomena such as code-mixing, the use of slang, and the dominance of foreign terms in the formal sphere show that Indonesian continues to develop following the dynamics of globalization. This research aims to analyze how the linguistic development of Indonesian in the digital era affects the structure, meaning, and function of communication in society. The research methods used are literature review and phenomenological analysis of language use in social media, the world of work, and the tourism sector. The results show that although the digital era enriches vocabulary and communication expressions, there are challenges in preserving Indonesian as a national identity. The increasingly dominant influence of foreign languages has the potential to shift the use of Indonesian in formal and academic domains. Therefore, an adaptive language policy strategy is needed, including digital literacy education and increasing public linguistic awareness, to maintain a balance between the development and preservation of Indonesian.